(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article explores the lexical-semantic field of the concept "joy" in the English language, analyzing how various words and expressions capture different facets of joy, from fleeting happiness to profound elation. It examines terms like "happiness," "delight," "euphoria," "ecstasy," and "bliss," as well as idiomatic expressions and cultural influences that shape their usage. The study highlights the complex nature of joy and the ways in which language reflects and conveys human emotional experiences.